Kinetic determinants of athletics sprint start performance - Salo, A. I. T.; Colyer, S. L.; Chen, P.; Davies, A. M.; Morgan, M. F.; Page, S. (ISBS Proceedings Archive (Michigan), 2017)
The sprint start lays a foundation to a good performance of track athletes. Thus, the aim was to understand the key force production determinants of the athletics sprint start. Eleven male athletes performed normal sprint starts with ground reaction forces collected at 1000 Hz from under each extremity separately. Key kinetic variables were analysed from six starts from each athlete and correlated with the horizontal external power. Several force and timing variables provided statistically significant correlations, but especially the high ratio of forces at 58.9 ± 3.5% with r = .941 (p = .000) demonstrated the importance of horizontal force production during the start. Better performers reached large forces on the blocks quicker, although it was interesting that the actual rate of force production did not statistically significantly correlate with the horizontal external power.